PROSEDUR TAKING ORDER OLEH FOOD AND BEVERAGE SERVICE PADA SPICE RESTAURANT NIRWANA GARDENS RESORT BINTAN - Halyati "; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Taking order is part of a very important service. Because through taking order waiters can find out the wishes and needs of guests. This study aims to know the procedure of taking order and to know obtacles of taking order by food and beverage service at Spice Restaurant Nirwana Gardens Resort Bintan. This research used descriptive qualitative method. The key Informant is outlet manager, supervisor, senior waiter, and waitress. Data collection was taken by direct observation, interviews, and documentation. Data analysis was done with data reduction, data display and conclusion. The results of this study show that: 1) the taking order procedure at Spice Restaurant has been running quite well; 2) Solutions to overcome obstacles to taking orders include: manual taking order when situational constraints occur; More focus, calm, and patient in facing guests; Added waiters are needed when the guests are busy; The need for training to facilitate foreign language by management; The waiters should be more professional and be able to separate personal affairs from work.Keyword: Procedure, Taking Order, Food and Beverage, Restaurant